A glimpse into the interactions of cells in a microenvironment: the modulation of T cells by mesenchymal stem cells - Choi, Jonghoon; Hwang, Mintai P.; Lee, Jong-Wook; Lee, Kwan Hyi (DOVE MEDICAL PRESS LTD, 2014)
Mesenchymal stem cells (MSCs) have been thought to hold potential as a mode of therapy for immuno-related pathologies, particularly for autoimmune diseases. Despite their potential, the interaction between MSCs and T cells, key players in the pathophysiology of autoimmune diseases, is not yet well understood, thereby preventing further clinical progress. A major obstacle is the highly heterogeneous nature of MSCs in vitro. Unfortunately, bulk assays do not provide information with regard to cell-cell contributions that may play a critical role in the overall cellular response. To address these issues, we investigated the interaction between smaller subsets of MSCs and CD4 T cells in a microwell array. We demonstrate that MSCs appear capable of modulating the T cell proliferation rate in response to persistent cell-cell interactions, and we anticipate the use of our microwell array in the classification of subpopulations within MSCs, ultimately leading to specific therapeutic interventions.
Keywords: IMMUNOMODULATORY PROPERTIES